Hydrous ferric oxide composite-integrated surface plasmon resonance sensor for arsenic ion detection - Flayih, Sura Hmoud (2018)
Heavy metal contamination is undoubtedly a major global threat that has sparked ecological and public health concerns. High exposure to heavy metals may cause chronic degenerative diseases that can cause permanent damage to the organ systems and leads to death. Heavy metals that are mostly found as contaminants in the environment would be arsenic (As) and plumbum (Pb). In response to this dire situation, detection and monitoring of these dangerous elements have become a vital necessity. Surface plasmon resonance (SPR) spectroscopy is a sensing technique that has gained exponential research interest especially in biological and chemical diagnostics. The technique is known for its high sensitivity in characterizing thickness and refractive index of a dielectric medium by analysing the resultant angular shift of the SPR output curve. What is more intriguing is the design of SPR and the proximity of the sensing region with the sample which would allow the incorporation of nanomaterials for sensing performance enhancement to detect lower than 0.6 ppb concentration of As in drinking water. This research work demonstrated the development of prism-based SPR sensor integrated with nanocomposites for the detection of As ions utilizing gold (Au) layer. Nanocomposites that were tested include hydrous ferric oxide (Fe2H2O4), hydrous ferric oxide-multiwalled carbon nanotube (Fe2H2O4-MWCNT) and hydrous ferric oxidemaghemite– reduced graphene oxide (Fe2H2O4-Fe3O4-rGO). Sensing performance of each nanocomposite layer was analyzed by introducing different concentrations of As(III) and As(V) within the range of 0.1 – 1.0 ppb. The sensitivity values for Au/Fe2H2O4 when tested with As(III) and As(V) were 1.640 °ppb-1 and 1.363 °ppb-1, respectively, with a detection limit of 0.6 ppb for both ions. The research work was continued with analysing the sensing performance of Au/Fe2H2O4-MWCNT nanocomposite. Based on the experimental results, sensitivity values for As(III) and As(V) were achieved at 1.756 ºppb−1 and 0.575 ºppb−1, respectively, with an enhanced limit of detection value at 0.2 ppb. The final nanocomposite sensing layer, Au/Fe2H2O4-Fe3O4-rGO, was conducted and the sensitivity values of 2.155 ºppb-1 and 1.190 ºppb-1 were obtained for As(III) and As(V), respectively. It is worth to note that the sensing performance from this nanocomposite managed to achieve the lowest detection limit for both As ions at 0.1 ppb. Based on these findings, the SPR technique incorporating nanomaterials have shown reliable performance as an As sensor. It is anticipated that this work may contribute greatly towards better As detection methods.